Precise Sub-Angstrom Ion Separation Using Conjugated Microporous Polymer Membranes - Zhou, Zongyao; Guo, Dong; Shinde, Digambar B; Cao, Li; Li, Zhen; Li, Xiang; Lu, Dongwei; Lai, Zhiping (ACS nano, 2021)
Polymer membranes typically possess a broad pore-size distribution that leads to much lower selectivity in ion separation when compared to membranes made of crystalline porous materials; however, they are highly desirable because of their easy processability and low cost. Herein, we demonstrate the fabrication of ion-sieving membranes based on a polycarbazole-type conjugated microporous polymer using an easy to scale-up electropolymerization strategy. The membranes exhibited high uniform sub-nanometer pores and a precisely tunable membrane thickness, yielding a high ion-sieving performance with a sub-1 Å size precision. Both experimental results and molecular simulations suggested that the impressive ion-sieving performance of the CMP membranes originates from their uniform and narrow pore-size distribution.